A law made by Italian mothers for Italian mothers? Women politicians and the 1950 law on maternity rights. Issue 1 (1st March 2016) - Schievenin, Pamela
Abstract : The development of welfare policies aimed at mothers and children has been deeply influenced by women's agency. This article explores the role played by Italian women politicians in the passing of the 1950 law on maternity rights. It examines the campaigns conducted by both left-wing and Catholic women, 1 and discusses the arguments and strategies they used to ensure that this gendered issue was on the political agenda. Particular attention is given to the parliamentary history of this legislation. While the law was being debated antagonism between the parties was at its height, and competition between the opposing women's organisations was fierce. Despite this, at a parliamentary level cross-party collaboration between women politicians was possible on this specific issue and was a crucial factor in the law being passed. Italian Abstract: Lo sviluppo di politiche sociali per la maternità e l'infanzia è stato profondamente influenzato dall'azione delle donne. Questo articolo esplora il ruolo svolto dalle 'donne politiche' italiane nell'approvazione della legge sulla tutela della maternità del 1950. Vengono esaminate le campagne portate avanti sia dalle donne di sinistra che dalle donne cattoliche. Vengono inoltre analizzate le argomentazioni e le strategie di cui le donne politiche si servirono per fare in modo che questa questione femminile diventasse parte dell'agenda politica. Particolare attenzione è rivolta all'iter parlamentare di questa normativa. Mentre la legge veniva dibattuta, la contrapposizione fra i partiti era al suo apice, e le organizzazioni femminili erano in forte competizione tra loro. Ciononostante, a livello parlamentare, una collaborazione trasversale tra donne è stata possibile su questa specifica questione, ed è stata un fattore decisivo per l'approvazione della legge.